PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS PADA SISWA KELAS III SDN 8 MAMBORO - Khaira, Lisatul; Nasrullah; Pahriadi; Zulnuraini; Andhika Pratama, Ryan (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study was to determine the effect of the use of audiovisual media on student learning outcomes in science learning in grade III students of SDN 8 Mamboro. This type of research is a quantitative experimental research using the Quasi-experimental research method with a Nonequivalent Control Group Design research design. The subjects in this study were 38 students of grade III A and III B of SDN 8 Mamboro. The control class or class III A students numbered 20 people and the experimental class or class III B students numbered 18 people. Data collection was carried out using a research instrument in the form of a test. Data analysis used prerequisite tests, namely normality tests and homogeneity tests and hypothesis testing using independent sample t-tests assisted by the IBM SPSS statistical application program version 24. Based on the results of this study, a significant value of 0.008 <0.05 was obtained, then the hypothesis Ha was accepted and Ho was rejected, meaning that there was an effect of the use of audio-visual media on student learning outcomes in science learning in grade III students of SDN 8 Mamboro. Keyword: Audio Visual Media, Student Learning Outcomes. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan media audio visual terhadap hasil belajar siswa dalam pembelajaran IPAS pada siswa kelas III SDN 8 Mamboro. Jenis penelitian ini adalah penelitian kuantitatif eksperimen menggunakan metode Quasi eksperimen research dengan desain penelitian Nonequivalent Control Group Design. Subjek pada penelitian ini yaitu siswa kelas III A dan III B SDN 8 Mamboro yang berjumlah 38 orang. Siswa kelas kontrol atau kelas III A berjumlah 20 orang dan kelas eksperimen atau kelas III B berjumlah 18 orang. Pengambilan data yang dilakukan menggunakan instrumen penelitian berupa tes. Analisis data menggunakan uji prasyarat yaitu uji normalitas dan uji homogenitas serta pengujian hipotesis menggunakan uji independent sample t-test berbantuan program aplikasi IBM SPSS statistic versi 24. Berdasarkan hasil penelitian ini menunjukkan nilai signifikan 0,008 < 0,05 maka menerima hipotesis Ha dan menolak Ho, artinya adanya pengaruh penggunaan media audio visual terhadap hasil belajar siswa dalam pembelajaran IPAS pada siswa kelas III SDN 8 Mamboro. Kata Kunci: Media Audio Visual, Hasil Belajar Siswa dan Pembelajaran IPAS